The Accuracy of Indonesian New Local Skin Prick Test (SPT) Allergen Extracts as Diagnostic Tool of IgE-mediated Atopic Dermatitis - Sylvia Anggraeni; Menul Ayu Umborowati; Damayanti; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Skin Prick Test (SPT) is good diagnostic tool of allergic disease such as Atopic Dermatitis (AD). Imported allergen extracts are expensive and not always available in Indonesia. New local SPT allergen extracts are potential as substitute. Objective: To compare SPT results of new local and imported allergen extracts (house dust mite, chicken, egg white, cow’s milk, and shrimp), and specific IgE in AD patients. Methods: This was clinical trial of 45 non lesional AD patients. The SPT of imported allergen extracts was performed in the first week, followed by the new local and specific IgE examination in the next one week. Result: Sensitivity (Sn) of new local compared with imported allergen extracts in this study was between 15.38%-84.61%, the highest point was house dust mite extract. Specificity (Sp) was ranged from 81.48%-93.75%, the highest rank was shrimp extract. Compared with IgE results, the Sn of new local and imported house dust mite extracts was good (85.7%; 92.9%). The Sp was good for egg white and cow’s milk new local extracts (86.4%; 84.4%). Conclusion: New local allergen extracts should be considered as a substitute of the imported diagnostic tool.